1977
DOI: 10.4141/cjps77-060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Row Spacing and Seeding Rates on Seed Yield in Red Clover, Alsike Clover and Birdsfoot Trefoil

Abstract: Peuxrw, P., BoNtN, S. G. rNo Lrsvnnsp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…While only five papers correlated the seed set with the bee visitation (i.e., Forster and Hadfield 1958;Free 1965;Palmer-Jones et al 1966;Clifford and Scott 1989;Lundin et al 2013). None of Battle (1949), Free (1965), Pankiw et al (1977), Puri and Laidlaw (1983), Puri and Laidlaw (1984), Leduc (1990), Rao and Stephen (2009) Seed number per pod of the floret Seed Seeds per pod Dijkstra (1969) and Richards (2016) Seeds per floret Oliva et al (1994) Seed number per flower head Seed Seed set Hawkins (1961), Clifford and Scott (1989) and Gillespie et al (2015) Seed yield per flower head g Fertility Meglic and Smith (1992) the studies measured the stigmatic pollen deposition in red clover, indicating limited information at the floret level. Due to the generally poor information level of pollination in the studies we surveyed, more research and specific evidence are needed to clarify the role of pollination on seed yield in red clover.…”
Section: Pollination Conditionsmentioning
confidence: 99%
“…While only five papers correlated the seed set with the bee visitation (i.e., Forster and Hadfield 1958;Free 1965;Palmer-Jones et al 1966;Clifford and Scott 1989;Lundin et al 2013). None of Battle (1949), Free (1965), Pankiw et al (1977), Puri and Laidlaw (1983), Puri and Laidlaw (1984), Leduc (1990), Rao and Stephen (2009) Seed number per pod of the floret Seed Seeds per pod Dijkstra (1969) and Richards (2016) Seeds per floret Oliva et al (1994) Seed number per flower head Seed Seed set Hawkins (1961), Clifford and Scott (1989) and Gillespie et al (2015) Seed yield per flower head g Fertility Meglic and Smith (1992) the studies measured the stigmatic pollen deposition in red clover, indicating limited information at the floret level. Due to the generally poor information level of pollination in the studies we surveyed, more research and specific evidence are needed to clarify the role of pollination on seed yield in red clover.…”
Section: Pollination Conditionsmentioning
confidence: 99%
“…As for the influence of seed yield components on seed yield, there seemed to be consistency between snow clover and red clover. In the latter, the total number of floral heads was reported to affect seed yield (Pankiw et al 1977;Montardo et al 2003) and it was suggested as a useful character for the yield improvement (Herrmann et al 2006), while both the number of stems per plant and the number of seeds per head were correlated with seed yield (Nasab and Jafari 2005).…”
mentioning
confidence: 99%
“…Very wide ranges of seeding rates are reported for red clover in literature but they are generally lower than those recommended here. Most frequent recommendations are between 2.0-4.5 kg ha -1 (Pankiw et al, 1977;Bowley et al, 1985;Bouet, Sicard, 1998;Huebner, 2016). Nevertheless, in real practices, the seed crops are usually sown at higher rates of 6-13 kg ha -1 to ensure establishment of crop stand (Rinker, Rampton, 1985;Huebner, 2016).…”
Section: Introductionmentioning
confidence: 99%